2x+-3y(6x-11)=-7

Simple and best practice solution for 2x+-3y(6x-11)=-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+-3y(6x-11)=-7 equation:


Simplifying
2x + -3y(6x + -11) = -7

Reorder the terms:
2x + -3y(-11 + 6x) = -7
2x + (-11 * -3y + 6x * -3y) = -7

Reorder the terms:
2x + (-18xy + 33y) = -7
2x + (-18xy + 33y) = -7

Solving
2x + -18xy + 33y = -7

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-33y' to each side of the equation.
2x + -18xy + 33y + -33y = -7 + -33y

Combine like terms: 33y + -33y = 0
2x + -18xy + 0 = -7 + -33y
2x + -18xy = -7 + -33y

Reorder the terms:
7 + 2x + -18xy + 33y = -7 + -33y + 7 + 33y

Reorder the terms:
7 + 2x + -18xy + 33y = -7 + 7 + -33y + 33y

Combine like terms: -7 + 7 = 0
7 + 2x + -18xy + 33y = 0 + -33y + 33y
7 + 2x + -18xy + 33y = -33y + 33y

Combine like terms: -33y + 33y = 0
7 + 2x + -18xy + 33y = 0

The solution to this equation could not be determined.

See similar equations:

| (6x^2)-30x=0 | | (6x^2)-30y=0 | | (6x+48)=(12x+24) | | 26.2=9t | | 3b-3-4b=2 | | 10=1+r+5 | | y=4+0.01x | | x^4-2x^2-6x+3=0 | | 3z+6=5z-4 | | 26+3n=-2(n+2)-n | | X^3+13=6x | | 23=2u-11 | | (8x-20)+(3x+15)=88 | | 36=5(w+3)-8w | | 3a+a=4*2 | | 2x+48=9x+13 | | y=10-0.01x | | 5x-2-3x=3x-3-8 | | 7b-15=5b-s | | 5a+3b-c= | | 289= | | 4x+5y=126 | | 7x-4y=18 | | 11*(6x+11)= | | -95=5z | | d+5=17-8+6 | | 2x^4+9x-18=0 | | 2(-4+7x)=34 | | .75t+.125=.75t*6 | | -4x-6=-16-6x | | 2(5y-1)+y=4(y-5)-3 | | x^4=9.14 |

Equations solver categories